واقع وﺁفاق الاقتصاد العالمي الجديد في ظل تداعيات الحرب الروسية والأوكرانية – دراسة تحليلية خلال الفترة 2020 – 2024: The reality and prospects of the new global economy in light of the repercussions of the Russian and Ukrainian war - an analytical study during the period 2020-2024 - طويل آسيا; محمد خضر الشطي (Journal of North African Economies, 2025)
The research focus of the Russian and Ukrainian war on the world economy by presenting realities and prospects in the current changes. After addressing Russia and Ukraine's economic status and that of the world, as one of the most serious repercussions of this new crisis, it will hinder and damage the growth and development of the global economic wheel, and increase the inflation rate that some European countries have begun to experience. This poses problems to the world economy which will identified. The study relies on the descriptive and analytical approach through the theoretical aspect of the world economy and the Russia-Ukraine War. Besides, the applied aspect through an analytical study, where the study ultimately found that the conflict’s results were passed on to the rest of the world. The impact has gone beyond to include a change in international alliances and political forces and a change in the map of international trade. Perhaps the positive impact is in activating communication in an integrated manner through visual communication (virtual communication), trade via e-mail and personal delivery.